Edukasi integrasi aplikasi perkantoran bagi mahasiswa - Maulana, Yoppy Mirza (Universitas Pendidikan Indonesia (UPI), 2023)
In this modern era, all organizations carrying out their administrative activities use computer-based office applications (AP). Like educational organizations, administrative activities include making reports on student study results, while business organizations, such as making sales reports, all these activities use AP. However, currently AP is not enough, there is a need for integrated AP (IAP). IAP is an activity that combines two or more APs. One application that supports this IAP is Microsoft Office. However, the fact is that in completing administrative work there are still people working in one AP, giving rise to problems of inefficiency and ineffectiveness. Therefore, this education aims to increase knowledge about IAP for students. This education is carried out online using lecture, practice, and question and answer methods, while evaluation using pre-test, post-test, and feedback methods. As a result of this educational evaluation, participants experienced an increase in knowledge about IAP as shown by the average pre-test score of 49% to an average post-test score of 77%. The increase in IAP knowledge has an impact on participants' knowledge and practice regarding object linking and embedding (OLE). Meanwhile, the average feedback results for this educational process show a strongly agree and agree figure of 98% and 2% disagree.